Exploring the blockchain for sustainable food supply chain. Issue 7 (3rd October 2022) - Roy, Rita; Chekuri, Kavitha; Sandhya, G.; Pal, Surya Kant; Mukherjee, Subhodeep; Marada, Nitish
Abstract: Blockchain Technology will bring a revolutionary change to the food supply chain (FSC). It will improve the visibility and traceability of the flow of food products. This study examined blockchain technology adoption in food supply chain industries in India. This study tried to examine the traceability of the food products across the food supply chain by using blockchain technology. This study will be beneficial to food industries who are thinking for a tracing and tracking mechanisms. The result shows the positivity for blockchain technology adoption in FSC industries. Also, it laid the foundation for blockchain technology adoption in FSC industries to achieve operational excellence. This study shows that with the adoption of blockchain FSC sectors can achieve sustainability in their operations and supply chain.